Atopic disorders in ankylosing spondylitis and rheumatoid arthritis. Issue 11 (1st November 2002) - Rudwaleit, M; Andermann, B; Alten, R; Sörensen, H; Listing, J; Zink, A; Sieper, J; Braun, J
Abstract : Background: The prevalence of atopic disorders in ankylosing spondylitis (AS) is unknown. AS and rheumatoid arthritis (RA) exhibit divergent T helper (Th) cell cytokine patterns. Objective: To test the hypothesis that Th2 polarised atopic disorders may be decreased in Th1 polarised RA but increased in AS, which is characterised by an impaired Th1 cytokine pattern, by assessing the prevalence of atopic disorders in AS and RA. Methods: 2008 subjects (380 patients with AS, 728 patients with RA, 900 controls) from Berlin, Germany, were considered in this cross sectional study. A questionnaire incorporating questions from the European Community Respiratory Health Service (ECRHS) and the International Study of Asthma and Allergies in Childhood (ISAAC) protocol was mailed to all subjects. Disease severity was assessed by the modified Health Assessment Questionnaire (mHAQ). Results: 1271 (63.3%) people responded to the questionnaire. The prevalence of any atopic disorder was 24.6% (61/248) in patients with AS, 20.7% (111/536) in controls, and 13.1% (64/487) in patients with RA (p=0.0009 for AS v RA; p=0.001 for controls v RA). Hay fever was reported by 40/248 (16.1%) patients with AS, 82/536 (15.3%) controls, and 42/487 (8.6%) patients with RA (p=0.002 for AS v RA; p=0.001 for controls v RA). Atopic dermatitis was reported by 19/248 (7.7%) patients with AS, 26/536 (4.9%) controls, and 14/487 (2.9%) patients with RA (p=0.003 for AS v RA), and asthma by 18/248 (7.3%) patients with AS, 35/536 (6.5%) controls, and 21/487 (4.3%) patients with RA. The differences were related neither to age nor to drugs. Disease severity was less in atopic patients with RA who had the atopic disorder before the onset of RA (median mHAQ 0.75) than in patients in whom RA preceded the atopic disorder (median mHAQ 1.75; p=0.027). Conclusions: Atopic disorders are decreased in RA but only slightly and non-significantly increased in AS. This may imply that atopy confers some protection from RA but only little if any susceptibility to AS. It may further indicate that the cytokine deviation towards an impaired Th1 pattern in AS is less strong than the cytokine deviation towards Th1 in RA, a finding which may affect future therapeutic approaches.